Chorreras. Eine phönizische Niederlassung östlich der Algarrobo-Mündung - Aubet, Maria Eugenia; Maass-Lindemann, Gerta; Schubart, Hermanfrid (Madrider Mitteilungen, 2021)
Deutsche Zusammenfassung folgt.